Evaluation of a haemozoin-based rapid diagnostic test for diagnosis of imported malaria during the phase of prevention of reestablishment in Sri Lanka - Deepika Fernando; Priyaleela Thota; Saveen Semege; Rahuman Booso; David Bell; Kumudunayana T. de A. W. Gunasekera; Prasad Ranaweera (Malaria Journal, 2022)
Abstract Background Sri Lanka, an island nation, has eliminated endemic malaria transmission. Maintaining elimination in the continued presence of vectors requires vigilance in screening people travelling from high malaria-risk areas and a rapid response with focal screening for infections identified in the community. Such screening requires accurate and very rapid assays that enable an immediate response. Both microscopy and rapid diagnostic tests (RDTs) have limitations including sensitivity and speed in screening large numbers, while polymerase chain reaction (PCR) is practical only as laboratory confirmation. This study assessed the utility of ‘Gazelle’, a novel rapid malaria assay based on magneto-optical detection of haemozoin, a by-product of malaria parasite metabolism. Methods Between October 2020 and March 2021, two groups of individuals were screened for malaria by four methods, namely, microscopy, Rapid Diagnostic Test (RDT), Gazelle and PCR. Passive case detection was carried out for confirmation of diagnosis amongst individuals suspected of having malaria. Individuals at high-risk of acquiring malaria, namely persons returning from malaria endemic countries, were screened by active case detection. Results Of the 440 individuals screened for malaria, nine malaria positives were diagnosed by PCR, microscopy and the HRP2 band of RDT, which included five Plasmodium falciparum infections, two Plasmodium ovale, and one each of Plasmodium vivax and Plasmodium malariae. Gazelle correctly detected the P. vivax, P. ovale and P. malariae infections within the 2 min test time, but did not detect two P. falciparum infections giving a sensitivity of 77.8%. Specificity was 100%. Discussion The Gazelle, a portable bench top device proved useful to screen a large number of blood samples for non-falciparum parasites within 5 minutes of sample input. Species differentiation, and improvement in P. falciparum detection, will be important to broaden utility.